Digging pitch, Brighton, Trinidad - (:unkn) unknown (My University, 2010)
Photo of blue collar workers digging pitch near tracks used to transport the asphalt at Brighton, Trinidad. Postcard also includes hand-written correspondence.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Asphalt industry--Trinidad and Tobago; Blue collar workers--Trinidad and Tobago; Railroads--Trinidad and Tobago; 1938; Villages--Trinidad and Tobago--Brighton; Pitch Lake, The (La Brea)